Geothermal steam condition performance monitoring. (September 2019) - Morris, C.J.; Mroczek, E.K.; Misa, T.N.
Highlights: Field data showed significant differences to separator design and scrubbing theory. There are no reliable measures of wet steam purity, though Na in the condensate is still the simplest. Steam washing does not necessarily improve purity to prevent turbine scaling. Reduction in turbulence in the 2-phase fluid before the separator improves purity. Abstract: Turbine scaling from poor purity steam is a major problem in geothermal power stations. The "true" purity and quality of steam going into geothermal turbines can't easily be measured in stations equipped with direct-contact condensers. Field testing has also shown that wet steam line samples are generally not representative of steam purity. Measuring sodium flux or chemical tracer injected upstream of the separators in drainpot condensate discharges can be used to determine the steam condition. However, the best measurement method seems to be the measuring of sodium flux. Tracers injected upstream of separators can take a long time to stabilise. The results of tracer studies need to be treated with caution and if they are used for a short interval test, they can give misleadingly optimistic results. Even with reliable representative data, there are very few changes that can be made to improve steam purity or quality without either major capital expenditure or significant load loss. This means that the design of a steam delivery system capable of providing clean dry steam is of vital importance in power station design. Results from existing stations' performance shows that the design of steam delivery systems is currently being poorly done.